"I don't see colour" : teacher discourses of integration in a selection of desegregated schools in Cape Town - Davies, Claire Thandi (Department of Sociology, 2015)
This thesis examines the discourses twenty three teachers in desegregated classrooms in Cape Town schools adopt toward integration and various constructions of difference. Discourse analysis reveals how the constructions of language, class and culture are being positioned as signifiers for difference, in place of race. Teachers tend either towards 'colour-consciousness 'or 'colour-blindness' in their discourses of race, and many white teachers demonstrate equality approaches toward different learners. Language as a difference is being used as a 'gate-keeper' to resist integration in schools. The construction of the past is problematic among some teachers, with the tendency to evade impacts the past still has on learners today.